Profil Ketahanan Ekonomi Rumah Tangga di Masa Pandemi Covid-19 Berdasarkan Tingkat Pendidikan dan Jenis Pekerjaan (Studi Kasus Kecamatan Sukajadi Kota Bandung) - putranida, shidqy fauzan; Nugraha, Reza Nanda (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2022)
In the microeconomic aspect, one of the impacts of the Covid-19 pandemic has hit family economic resilience. Economic resilience is a condition of the nation's economic life where people must be able to survive in overcoming all threats, disturbances, obstacles and challenges. This qualitative study aims to analyze the economic resilience of families in Sukajadi District, Bandung City. The technique for collecting data is using a convenience sampling technique using a questionnaire instrument, then data analysis using a descriptive method. The number of respondents was 832 heads of household. The variables used are the level of education and type of work. The results showed that the pandemic had an impact on all heads of households with education levels ranging from elementary to university and any type of work. However, in Sukajadi Sub-district, the education level of SMA/equivalent is the most affected by the COVID-19 pandemic, while the type of work most affected is the type of non-permanent work. Following up on the findings of this study, the government can participate in formulating policies that will be made to increase household economic resilience.